GH overexpression causes muscle hypertrophy independent from local IGF-I in a zebrafish transgenic model - Kuradomi, Rafael Yutaka (2013)
Submitted by Cristina Damasceno (damascenocris2011@gmail.com) on 2012-11-13T00:47:33Z No. of bitstreams: 1 GH overexpression causes muscle hypertrophy independent from local IGF-I in a zebrafish transgenic model.pdf: 267366 bytes, checksum: 8e88730d0e77330daeda83a5e4e0d9c5 (MD5)